2020
DOI: 10.1038/s41598-020-64563-7
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobicity and size reduction enabled Halobates (Insecta: Heteroptera, Gerridae) to colonize the open ocean

Abstract: Despite the remarkable evolutionary success of insects at colonizing every conceivable terrestrial and aquatic habitat, only five Halobates (Heteroptera: Gerridae) species (~0.0001% of all known insect species) have succeeded at colonizing the open ocean-the largest biome on earth. this remarkable evolutionary achievement likely required unique adaptations for them to survive and thrive in the challenging oceanic environment. For the first time, we explore the morphology and behavior of an open-ocean Halobates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 69 publications
2
34
0
Order By: Relevance
“…As the fly drifts away from the collision site, it rolls on the pool making several attempts to stand ( –400 ms). The fly manages to stand in less than a second and quickly leaps into flight ( –600 ms) by moving its four hind legs in a rowing-like jump, similar to that of a water strider 11 , 28 (Supplementary video 8 ; the jumping motion is smoother in some other observations). In all observations, the flies never stay on the pool surface for more than a couple of seconds (Table 1 ) and do not exhibit any kind of water walking motion, seeming to prefer to locomote in the air and rest on solid surfaces.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…As the fly drifts away from the collision site, it rolls on the pool making several attempts to stand ( –400 ms). The fly manages to stand in less than a second and quickly leaps into flight ( –600 ms) by moving its four hind legs in a rowing-like jump, similar to that of a water strider 11 , 28 (Supplementary video 8 ; the jumping motion is smoother in some other observations). In all observations, the flies never stay on the pool surface for more than a couple of seconds (Table 1 ) and do not exhibit any kind of water walking motion, seeming to prefer to locomote in the air and rest on solid surfaces.…”
Section: Resultsmentioning
confidence: 95%
“…Augmenting chemistry with roughness can increase the apparent contact angle 8 , and superhydrophobicity ( ) occurs when air becomes entrapped in the valleys of roughness elements (Cassie wetting) with increasing air fraction raising 9 . Many insects take advantage of this wetting physics and attain superhydrophobicity by both coating their bodies with oil or wax to optimize their surface chemistry 3 , 10 , 11 , and using hierarchical roughness structures to maximize the air fraction (minimize the solid-liquid contact) between the liquid and their bodies 4 . The roughness appears in many forms in insects and plants alike, including: nanopillars on drone fly 12 and dragonfly wings 13 , micropapillae on lotus leaves 14 , micropapillae with nanofolds on rose petals 15 , needle shaped setae with nanogrooves on water strider 11 , 16 and crane fly legs 17 , and arrays of hair with star-shaped cuticular projections on termite wings 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water striders live on the water's surface, using microsetae, fine hydrophobic hairs, to maintain buoyancy and allow them to stride across the water (Kaitala 1987; Mahadik et al 2020). Disruption of this mechanism may lead to immobility and death: we observed that oil directly affected the strider's ability to skate across the water's surface.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a new class of microtextures has been developed, comprising microcavities that broaden below the inlets such that the cross‐section of the space between adjacent cavities spanning cavity inlets and the intervening wall resembles the serif‐T shape [ 7,16–22 ] ( Figure A–C). These bio‐inspired [ 18,23 ] microtextures are known as doubly reentrant cavities (DRCs), and they can entrap air inside them on immersion in liquids due to their topography, regardless of their surface make‐up. [ 21 ] In fact, the transition of these air‐filled cavities—Cassie‐states [ 24–26 ] to the fully‐filled or the Wenzel‐state [ 27 ] depends on a number of factors, such as the compressibility of the trapped air, liquid vapor pressure, capillary condensation, the solubility of the trapped air in the liquid, and the cavity geometry.…”
Section: Introductionmentioning
confidence: 99%